Comparative metabolic analysis of the adaptive Candida tropicalis to furfural stress response. (5th March 2023) - Wang, Le; Qi, Andong; Liu, Jianguang; Shen, Yan; Wang, Jinshui
Graphical abstract: Abstract: The novel tolerant strain Candida tropicalis Y31-N (Y31-N) with the high tolerance against furfural was obtained by the continuous domestication processes from the parent strain Candida tropicalis Y-3 (Y-3). The xylitol yield was increased by more than 84.8% with the Y31-N, as well as the furfural consumption at about five-times rate than the Y-3. The Y31-N was able to control the cells membrane fluidity by regulating the composition of the fatty acids in cells, thus maintaining the integrity of cells membrane function to resist furfural stress, and could produce more ATP and NAD(P)H rapidly through the metabolic rearrangement to alleviate the furfural stress, compared to the Y-3. Moreover, several genes related to trehalose synthesis, GABA metabolism and NADPH production were verified to be essential for resistance to furfural by single-gene knockout. It provided a broader understanding of the mechanisms of furfural tolerance and prospective evidence for the further metabolic engineering.